ENT300 24-Hours Laundry Service / Hudson Huan John... [et.al] - John, Hudson Huan; Osman, Zarifah; Merais, Muhammad Nur Syafiq; Buyong, Menissa (2016)
Our 24 Hour Self-Service Laundry provides laundry services such as washing and drying. To fit the title self-service laundry, customers are free to choose between three different temperature (hot, normal, cold) to wash their clothes according to the needs for the same price. Customers do not have to worry about having to carry their detergent and softener from home as it is provided for free. As for drying service, customers are able to add extra minutes of drying after the first 30 minutes allocated (to their own preference) to make sure their laundry are dried completely.